Heat shock response of Saccharomyces cerevisiae mutants altered in cyclic AMP-dependent protein phosphorylation. - Shin, D Y (1987)
When Saccharomyces cerevisiae cells grown at 23 degrees C were transferred to 36 degrees C, they initiated synthesis of heat shock proteins, acquired thermotolerance to a lethal heat treatment given after the temperature shift, and arrested their growth transiently at the G1 phase of the cell division cycle. The bcy1 mutant which resulted in production of cyclic AMP (cAMP)-independent protein kinase did not synthesize the three heat shock proteins hsp72A, hsp72B, and hsp41 after the temperature shift. The bcy1 cells failed to acquire thermotolerance to the lethal heat treatment and were not arrested at the G1 phase after the temperature shift. In contrast, the cyr1-2 mutant, which produced a low level of cAMP, constitutively produced three heat shock proteins and four other proteins without the temperature shift and was resistant to the lethal heat treatment. The results suggest that a decrease in the level of cAMP-dependent protein phosphorylation results in the heat shock response, including elevated synthesis of three heat shock proteins, acquisition of thermotolerance, and transient arrest of the cell cycle.